Impacts of heterogeneous HONO formation on radical sources and ozone chemistry in Houston, Texas. (July 2015) - Couzo, Evan; Lefer, Barry; Stutz, Jochen; Yarwood, Greg; Karamchandani, Prakash; Henderson, Barron; Vizuete, William
Abstract: The chemical mechanisms used in regulatory air quality models typically allow for only homogeneous formation of nitrous acid (HONO), an important radical precursor. This study adds heterogeneous formation on surfaces as a HONO source to the Comprehensive Air quality Model with extensions (CAMx). Modeling was performed for the Houston, Texas, region on April 21, 2009. Comparisons to measurements made at Moody Tower during the Study of Houston Atmospheric Radical Precursors (SHARP) show that adding heterogeneous formation increases HONO concentrations, particularly in the early morning and at night. Heterogeneous HONO formation reduces normalized mean error for morning, daytime, and nighttime HONO concentrations from 77% to 67%, 66%–28%, and 99%–67%. Maximum daily 8-hr O3 concentrations were up to 3.5 ppb greater as a result of heterogeneous HONO formation. Direct HONO emissions equal to 0.8% of NOx emissions were also added to the model, but they were considered separately from heterogeneous HONO formation. Increases over the base case of HONO and O3 were seen, though the magnitudes are not as great as with heterogeneous HONO formation. Maximum daily 8-hr O3 concentrations were up to 0.4 ppb greater than with homogeneous HONO formation alone. Significant early morning and nighttime HONO under predictions were seen compared to SHARP measurements in the direct emissions scenario. Direct HONO emissions led to local increases of HONO and O3 in areas with high NOx emissions, but heterogeneous HONO formation led to regional increases of both. Process analysis was used to determine the effect on O3 chemistry in downtown Houston. Daily total hydroxyl radical (OH) production from HONO photolysis was 3.94 ppb/day with heterogeneous HONO formation, 2.40 ppb/day with direct emissions, and 1.40 ppb/day in the base case. A 10% increase of hydrocarbon and carbon monoxide oxidation by OH was seen with heterogeneous HONO formation, while the increase in the direct emissions scenario was 3%. Nitric oxide (NO) to NO2 conversion increased by 8% with heterogeneous formation, while the increase was only 3% with direct HONO emissions. Radical sources, radical propagation, and oxidant production were enhanced at each step in the chemical cycle – particularly just after sunrise – by the addition of heterogeneous HONO formation and direct HONO emissions, but the effects were greater with heterogeneous formation. Highlights: Surface model provides a mechanistic approach to heterogeneous chemistry. Addition of heterogeneous HONO formation improves overnight/early morning model performance. Radical production and VOC oxidation increases substantially following sunrise. Direct HONO emissions are not sufficient to reproduce overnight/early morning measurements. Heterogeneous HONO formation increases ozone across the modeling domain.